Modelling and design of a novel air-spring for a suspension seat - Holtz, Marco Wilfried (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2008.